Equações diferenciais funcionais com retardamento e impulsos via equações diferenciais ordinárias generalizadas - Ginnara Mexia Souto (2013)
The purpose of this work is to investigate fundamental results and some qualitive properties of solutions of Retarded Functional Differential Equations with pre-assigned moments of impulsive effects (IRFDEs) using the theory of Generalized Ordinary Differential Equations (GODEs). Our main results concern continuous dependence on parameteres, uniform stability and uniform asymptotic stability of the solutions of a certain classs of IRFDEs. In order of obtain such results, we study the equivalence between IRFDEs and certain class of GODEs